2000
DOI: 10.1086/315589
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Classification of “Norwalk‐like Viruses”

Abstract: Reverse transcription-polymerase chain reaction has been used worldwide for the diagnosis of Norwalk-like virus (NLV) infection, yet a commonly accepted genetic classification scheme has not been established. Amino acid sequences from four regions of open-reading frame 2 (ORF2) were used to analyze 101 NLV strains, including 2 bovine strains. On the basis of this analysis, a genetic classification scheme is proposed that differentiates 99 human strains into 2 major genetic groups consisting of 5 and 10 genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
226
0
7

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 275 publications
(240 citation statements)
references
References 84 publications
7
226
0
7
Order By: Relevance
“…Antigenic and genetic variability is also a feature of other caliciviruses, especially the human noroviruses, where highly variable genogroups containing multiple genotypes are described [2,34]. The origins of this diversity are poorly understood.…”
Section: Aetiologymentioning
confidence: 99%
“…Antigenic and genetic variability is also a feature of other caliciviruses, especially the human noroviruses, where highly variable genogroups containing multiple genotypes are described [2,34]. The origins of this diversity are poorly understood.…”
Section: Aetiologymentioning
confidence: 99%
“…Recently, Ando et al [1] have proposed a genetic classification of human NLVs into 2 major genetic groups, genogroups GI and GII, consisting of 5 and 10 genetic clusters, respectively. In addition, they described a third genogroup, including 2 bovine strains, the Newbury Agent-2 (NA-2) and Jena/80 (JV).…”
Section: Introductionmentioning
confidence: 99%
“…The aim of the present study was to provide a genetic classification of SLV strains, using the same criteria and methodology as Ando et al [1] for their classification of NLVs. We sequenced 3-kb of the 3 half of the genome of 2 SLV strains detected in French infants and analysed these newly determined sequences, The SLV strains sequenced in this study are highlighted in bold.…”
Section: Introductionmentioning
confidence: 99%
“…Human NVs can be divided into two genogroups, genogroups GI and GII, by genetic analysis of the RNA polymerase and capsid regions (1, 15), with several genotype classifications having been reported independently (1,16,33). Recently, based on the genotype classification of Katayama et al (16), Kageyama et al (15) reported on a detailed scheme for the genotyping of NVs based on distribution analysis by using the pairwise distance of the capsid N-terminal/shell domain.…”
mentioning
confidence: 99%